Improving Reading Comprehension through Mind Mapping and Concept Mapping to the Tenth Grade Students of State Senior High School 1 of Kelapa Bangka - Juriana Juriana (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACTThis study dealt with the use of mind mapping and concept mapping as the one technique in teaching reading comprehension. The problems of this study were to find out whether or not there was any significant difference in average scores between students’ reading comprehension achievement who (1) both had been taught using conventional technique and mind mapping technique (2) both had been taught using conventional technique and concept mapping technique (3) had been taught using mind mapping technique and concept mapping technique (4) there is any significant difference among students who were taught using mind mapping, concept mapping, and conventional technique.The population was 160 students of the tenth grade students of State Senior High School 1 of Kelapa Bangka. Cluster random sampling was used to take 80 students as the sample. True Experimental Design was used as a method of the study. In collecting the data, tests were used. Homogeneity, normality, and independent sample t test were used to analyze the data.Based on the research, the writer concluded that the mind mapping technique and concept mapping technique were more effective and better for (1) students who were taught using mind mapping than students who were taught using conventional technique, (2) students who were taught using concept mapping than students who were taught using conventional technique, (3) students who were taught using mind mapping than students who were taught using concept mapping, and (4) since there was any significant difference among mind mapping, concept mapping, and conventional techniques, the technique is suitable to be used in improving students’ reading comprehension achievement. Key words: 1. Mind Mapping, 2. Concept Mapping, 3. Reading Comprehension